Metode Mind Mapping dalam Pembelajaran Bahasa Indonesia di MI: Bagaimana Pengaruhnya terhadap Hasil Belajar Peserta Didik? - Purnayanti, Hanik; Kusmawati, Heny (Sekolah Tinggi Agama Islam Pati, 2024)
This research discusses the influence of the Mind Maps Method on Student Learning Outcomes in Indonesian Language Subject Theme 8 Concerning Nonfiction Texts for Class V MI NU Bahrul Ulum Kudus for the 2021/2022 Academic Year. This research aims to determine the effect of the mind maps method on students' learning outcomes in Indonesian Language Topic 8 Concerning Nonfiction Texts for Class V MI NU Bahrul Ulum Kudus for the 2021/2022 academic year. This research is quantitative research with regression analysis techniques. The research population was 32 fifth grade students and the sample was 32 respondents. Data collection techniques use questionnaire, documentation and test methods. The research data collected was analyzed using inferential statistical analysis techniques.The results of the research show that the results of the regression calculations that have been found, the results of the b value are positive, indicating that variable If the mind maps method decreases, learning outcomes will also decrease. So, it is estimated that the learning outcomes of MI NU Bahrul Ulum Kudus students are Y = 1.196 + 0.792. From this regression equation, if the value of the mind maps method is added by one, then the value of the learning outcomes will increase by 0.792 or for every value of the mind maps method added by 10, the value of the learning outcomes will increase by 7.92. Meanwhile, the results of the research show that there is a mind maps method for student learning outcomes in the Indonesian language subject Theme 8 regarding Nonfiction Texts for Class V MI NU Bahrul Ulum Kudus for the 2021/2022 academic year. Based on the value of tcount ttable, it is (7.2082.04227). Supported by a significance value smaller than 0.05, which indicates a value of 0.000. This is shown from the product moment calculation, it turns out that the calculated price is greater than rtable, namely 0.796 0.349 at the 5% level, so it can be concluded that there is a positive relationship.The results of this research show that the Mind Map method has a positive and significant effect on students' learning outcomes in the Indonesian language subject Theme 8 Concerning Nonfiction Texts for Class V MI NU Bahrul Ulum Kudus for the 2021/2022 academic year.